THE ROLE OF BUDDHIST EDUCATION IN MONASTIC PRIMARY SCHOOLS: A CASE STUDY OF WAT PREY SPEU, CAMBODIA - Dr. By Loeung; Dr. Sophoeun Phal (jfpublisher, 2025)
Cambodia's educational system is deeply rooted in Buddhist tradition, with monasteries historically serving as learning centers that prioritize moral development and cultural preservation alongside academic subjects. This qualitative case study investigates the role of Buddhist education at Wat Prey Speu Buddhist Primary School, exploring how it integrates traditional precepts within the national curriculum. Thematic analysis was used to interpret data from in-depth interviews with 59 stakeholders, including students, teachers, and administrators. The findings reveal the school's primary strength is its holistic approach, which develops students' moral conduct (Sīla), concentration (Samādhi), and wisdom (Paññā). The institution also plays a vital role in preserving Khmer culture and providing affordable education to underserved communities. Key recommendations include formalizing the curriculum, addressing a significant gender imbalance, and seeking formal recognition and support from the Ministry of Education to promote this valuable educational model.